Analisis Peran Guru PAI dalam Membentuk Karakter Peserta Didik di Sekolah - Fadli, Fery; Albina, Meyniar (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The significant influence that Islamic Religious Education (PAI) teachers have on students' character development in the classroom will be discussed in this article. One of the most important components of education is character education, and PAI teachers play a key role in implementing this goal. The purpose of this study is to look at how PAI teachers influence students' personalities, the approaches they use, and the real-world applications of their teaching in the educational environment. Data were collected through observations in schools, interviews with PAI teachers, and literature review. The research findings show that by teaching religious principles, moral guidance, role modeling, and constructive relationships, PAI teachers play a strategic role in shaping students' characters. The practical implications of this study include the importance of increasing the involvement of PAI teachers. The practical implications of this study include enhancing the role of PAI teachers in character education, improving their credentials and competencies, and promoting collaboration between PAI teachers, schools, and parents in an effort to shape high-quality student character. Data were collected through a literature review.